Application Of The WBZ (Warm Belt Zinger) Method To The Intensity Of Labor Pain At The BL 31-32 Meridian Points In PMB Semarang City - Lestari Puji Astuti; Poppy Fransisca Amelia; Heny Wijayanti; Sa’adah Mujahidah (Humanistic Network for Science and Technology (HNST), 2020)
The research purposes to find out the effectiveness of WBZ (Warm Belt Zinger) and warm compresses at the meridian points BL 31 and 32 on the intensity of labor pain during. The pain that a woman experiences while entering labor is a physiological process. Labor pain is the most severe thing felt by women throughout their life. Non-pharmacological efforts are needed to reduce labor pain. Types of research was quasi-experiment with pretest-posttest with control design. The sampling technique used was accidental sampling with sample size of 30 people and divided into two groups intervention WBZ n=15 and control (warm compress) n=15. The subjects were the mothers who gave birth in were in the first phase of the active phase (4-10 cm opening). There was differences in first time pain in the maternity before and after the WBZ group (p-value = 0.000). There was a difference in first-time pain in the maternity before and after in the warm compress (p-value = 0.000). Statistical test results WBZ and warm compresses are effective for decrease the pain in first stage labor (p-value = 0.001). WBZ and warm compresses effective to reduce labor pain in the first stage. Keywords: ginger compress; warm compress; meridian points bl 31 and 32; intensity of labor pain